Does Surgery of the Olfactory Clefts Modify the Sense of Smell?. Issue 4 (July 2013) - Nguyen, Duc Trung; Gauchotte, Guillaume; Nguyen-Thi, Phi-Linh; Jankowski, Roger
Background: The olfactory outcome after surgery of polyps in the olfactory clefts (OCs) is unknown. This study was designed to (1) investigate the relationship between clinical characteristics and the presence of the respiratory epithelial adenomatoid hamartoma (REAH) in the OCs and (2) assess the olfactory outcome after surgery in the OC for either eosinophilic polyps (EP) or REAH in patients with ethmoidectomy for nasal polyposis (NP). Methods: Seventy-four patients with NP having undergone nasalization procedure were enrolled in this prospective study. The OCs were systematically examined during endoscopic surgery. Small polyps or edematous mucosa of the OC were systematically biopsied. Moderate or big polyps in the OC were removed after nasalization of the ethmoidal labyrinths. The distinction between REAH and EP relied on histopathological examinations. The olfactory function was measured with standardized odor threshold and identification tests 1 day before and 6 weeks after surgery. Results: There was a close relationship between the presence of REAH-OC and the duration of NP disease (p = 0.0009), asthma (p = 0.004), and previous surgery (p = 0.0006). Before surgery, 90.6% of patients with REAH-OC were hypo-anosmic in contrast with one-half of patients having EP-OC (p = 0.0003). Predictors of poor olfactory outcomes after surgery were long-standing nasal symptoms (p = 0.027), history of previous surgery (p = 0.01), and history of previous middle turbinates resection (p = 0.0006). Polyp histology and surgery of the OC were not predictors of poor olfactory outcomes. Conclusion: The resection of REAH or EP of the OC in patients with NP does not worsen but instead can improve the sense of smell after surgery.